Cytosolic phospholipase A2 contributes to innate immune defense against Candida albicans lung infection. (December 2016) - Jayaraja, Sabarirajan; Dakhama, Azzeddine; Yun, Bogeon; Ghosh, Moumita; Lee, HeeJung; Redente, Elizabeth; Uhlson, Charis; Murphy, Robert; Leslie, Christina
Abstract Background The lung is exposed to airborne fungal spores, and fungi that colonize the oral cavity such asCandida albicans, but does not develop disease to opportunistic fungal pathogens unless the immune system is compromised. The Group IVA cytosolic phospholipase A2 (cPLA2 α) is activated in response toCandida albicans infection resulting in the release of arachidonic acid for eicosanoid production. Although eicosanoids such as prostaglandins and leukotrienes modulate inflammation and immune responses, the role of cPLA2 α and eicosanoids in regulatingC. albicans lung infection is not understood. Methods The responses of cPLA2 α+/+ and cPLA2 α−/− Balb/c mice to intratracheal instillation ofC. albicans were compared. After challenge, we evaluated weight loss, organ fungal burden, and the recruitment of cells and the levels of cytokines and eicosanoids in bronchoalveolar lavage fluid. The ability of macrophages and neutrophils from cPLA2 α+/+ and cPLA2 α−/− mice to recognize and killC. albicans was also compared. Results AfterC. albicans instillation, cPLA2 α+/+ mice recovered a modest weight loss by 48 h and completely cleared fungi from the lung by 12 h with no dissemination to the kidneys. In cPLA2 α−/− mice, weight loss continued for 72 h, C. albicans was not completely cleared from the lung and disseminated to the kidneys. cPLA2 α−/− mice exhibited greater signs of inflammation including higher neutrophil influx, and elevated levels of albumin and pro-inflammatory cytokines/chemokines (IL1α, IL1β, TNFα, IL6, CSF2, CXCL1, CCL20) in bronchoalveolar lavage fluid. The amounts of cysteinyl leukotrienes, thromboxane B2 and prostaglandin E2 were significantly lower in bronchoalveolar lavage fluid fromC. albicans -infected cPLA2 α−/− mice compared to cPLA2 α+/+ mice. Alveolar macrophages and neutrophils from uninfected cPLA2 α−/− mice exhibited less killing ofC. albicans in vitro than cells from cPLA2 α+/+ mice. In addition alveolar macrophages from cPLA2 α−/− mice isolated 6 h after instillation of GFP-C. albicans contained fewer internalized fungi than cPLA2 α+/+ macrophages. Conclusions The results demonstrate that cPLA2 α contributes to immune surveillance and host defense in the lung to prevent infection by the commensal fungusC. albicans and to dampen inflammation.